Takhrij and Syarah Hadith of Chemistry: Alcohol Use Laws in Medicine - Anisa Nurhasanah; Riki Muhammad Fahmi; Muhlas Muhlas; Wahyudin Darmalaksana; Tina Dewi Rosahdi (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet Saw. about the use of alcohol in medicine. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this study is about the law of the use of alcohol in medicine which is often used in the medical field. The conclusion of this research is takhrij and syarah hadith of the Prophet Saw. about alcohol in drugs is allowed but does not contain addiction and intoxication, but only as a cure. The author recommends developing non-alcoholic drugs through chemistry.